Ab initio and diffusion Monte Carlo study of uracil-water, thymine-water, cytosine-water, and cytosine-(water)(2) - van Mourik, T; Benoit, D; Price, S; Clary, D (2000)
Optimized geometries, potential well depths, and harmonic zero-point energies of the uracil-water, thymine-water, cytosine-water, and cytosine- (water)2 weakly-bound molecules are computed using second-order Moller- Plesset perturbation theory and an interaction-optimized, singly-polarized double zeta basis set (DZPi). At the optimized geometries of the base-water structures, single point calculations ale carried out using the slightly larger ESPB basis set, which is a singly-polarized 'extended s' basis set, containing a set of (s,p) bond functions at the midpoint of each hydrogen bond. All structures are also optimized with a simple intermolecular potential model, consisting of a Lennard-Jones repulsion-dispersion term and a point-charge model for the electrostatic interaction. The ab initio energies are used to assess the realism of the model potential for computing structures and frequencies within the harmonic approximation. The weakness of the harmonic approximation for these weakly bound complexes was assessed by using this potential in rigid-body diffusion Monte Carlo simulations to obtain the anharmonic zero-point energies and vibrationally averaged geometries of the molecular systems investigated. It is found that, although the anharmonicity correction to the zero-point energy is fairly small, the intermolecular bonds are significantly affected by vibrational averaging.